1981
DOI: 10.1111/j.1365-246x.1981.tb02752.x
|View full text |Cite
|
Sign up to set email alerts
|

Some analyses of P- and Rayleigh wave amplitudes observed at North American stations

Abstract: Pand Rayleigh wave amplitudes observed by the Long Range Seismic Measurements network of stations in North America are analysed into source, distance and station effects.The main results of the P-wave analyses are:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Amplitudes of seismic waves are used to assess the seismic event magnitudes, and there has been a continuous effort to understand amplitude variations on local, regional and global levels. Studies of variations of the short period P ‐wave amplitudes across large seismic arrays such as LASA and NORSAR have shown that the amplitude of a given signal can differ by a factor of four or more between seismometers separated by only a few kilometres (Douglas et al 1981). Short period amplitudes of explosions closely located and of close yield can vary as much as 90 per cent (Romney 1959).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amplitudes of seismic waves are used to assess the seismic event magnitudes, and there has been a continuous effort to understand amplitude variations on local, regional and global levels. Studies of variations of the short period P ‐wave amplitudes across large seismic arrays such as LASA and NORSAR have shown that the amplitude of a given signal can differ by a factor of four or more between seismometers separated by only a few kilometres (Douglas et al 1981). Short period amplitudes of explosions closely located and of close yield can vary as much as 90 per cent (Romney 1959).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the difficulty in predicting amplitude fluctuations at individual sites, regional averages of magnitude residuals for short period waves were found to be still meaningful (Der et al 1982). Variations of long period P waves are less dramatic, and correlations with the geological character of the lithosphere or crust have been noted (Douglas et al 1981; Der et al 1982; Booth et al 1974; Lay & Helmberger 1981).…”
Section: Introductionmentioning
confidence: 99%
“…However there are several factors which contribute to the station effect which should be considered before any correIation is made with other geophysical observations. Douglas, Young & Marshall (1981) concluded in their analyses of station effects within North America that there are no contributions to the station effect from differences in the levels of seismic noise at the recording stations. In other words the station effect is not due to stations with high noise levels detecting only above average amplitudes and low noise stations detecting both above and below average amplitude signals.…”
mentioning
confidence: 99%